THE RELATIVE PROFITABILITY OF LARGE, MEDIUM-SIZED AND SMALL BUSINESS. - Osborn, Richards C. (The Accounting Review, 1950)
Abstract This article proposes to investigate, review, and analyze the data which have been compiled on the subject of profitability in relation to size to determine the foundation on which the statement of large corporations being unprofitable has been based, and to comment on the validity of the assertion as it relates to the relative profitableness of corporations of different size. Such an analysis must necessarily be limited to the objective material available and will not enter into the broader discussion of the social and economic evils usually associated with, and often attributed to, monopoly or big business. No attempt will be made to evaluate the proposition that large-scale business necessarily results in a power position which is so antisocial that a reduction in size would be warranted, regardless of the possible outcome for efficiency and profitability. Such matters can be settled satisfactorily only after long investigation and will involve complex analyses of broad social policy.